An integrated fuzzy ANP–QFD approach for green building assessment - Ignatius, Joshua; Rahman, Amirah; Yazdani, Morteza; Šaparauskas, Jonas; Haron, Syarmila Hany (Journal of Civil Engineering and Management, 2016)
One of the major concerns in the construction industry is the sustainability of building projects. There are various trade-offs between functionality and design, which often lead to an issue of whether sustainably designed buildings would meet stakeholder requirements. This paper provides a novel integrated structure for assessing green buildings realistically based on stakeholders’ fuzzy preferences. In particular, the paper uses the analytic network approach (ANP) to evaluate the correlation matrices in a quality function deployment (QFD) framework. A case study on green building index assessment in Malaysia illustrates the proposed integrated method. Sensitivity analysis validated the customer-stakeholder agreement towards the design of the green building. Cluster analysis was also used to group design specifications prior to the analysis.